2010
DOI: 10.1089/thy.2009.0408
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Recombinant Human Thyrotropin Potency Based on Bioassay in FRTL-5 Cells

Abstract: rhTSH kept at 4°C, -11°C, -60°C, and room temperature maintained good biologic potency for more than 6 months of storage when tested in vitro, indicating that the biologic activity is very stable. However, altered sialylation occurring during storage could have altered the half-life of rhTSH. Nevertheless, the data provide reassurance that storage in the cold for a few months does not result in significant loss of biologic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Results of the present study indicated that freezing-thawing, or cooling over a period of 6 months, did not significantly change the structure or biological activity of eCG. Similar to our results, Lin et al (2010) found that recombinant human TSH kept at 4, -11 and -60°C maintained good biological potency for more than 6 months of storage when tested in vitro, indicating that biological activity is very stable. Curiously, in this study, cold stressed TSH tended to show an increase in bioactivity in comparison with the control.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the present study indicated that freezing-thawing, or cooling over a period of 6 months, did not significantly change the structure or biological activity of eCG. Similar to our results, Lin et al (2010) found that recombinant human TSH kept at 4, -11 and -60°C maintained good biological potency for more than 6 months of storage when tested in vitro, indicating that biological activity is very stable. Curiously, in this study, cold stressed TSH tended to show an increase in bioactivity in comparison with the control.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is known that some proteins such as IgG can be refrigerated or frozen for long periods of time without significant loss of activity (Argüello et al, 2003). Furthermore, glycoprotein hormones such as pituitary FSH and LH (Reyna et al, 2001) or recombinant thyroid stimulating hormone (TSH; Lin et al, 2010) had no consistent or predictable alteration when subjected to repeated freezing-thawing cycles or long periods of refrigerated storage.…”
Section: Introductionmentioning
confidence: 99%
“…These FRTL-5 cells were grown in the six-hormone (6H) medium of Coon’s modified Ham’s F-12 supplemented with 5% calf serum, 2 mM glutamine, 1 mM nonessential amino acids, and the 6H mixture (6H5% medium): 1 mU/mL bovine TSH (Thyroid-stimulating hormone), 10 μg/mL insulin, 0.4 ng/mL cortisol, 5 μg/mL transferrin, 10 ng/mL glycyl-L-histidyl-L-lysine acetate, and 10 ng/mL somatostatin. These cells were diploid, between the 5th and 25th passage, and had all of the functional properties described previously [12,13,14,15,16]. Fresh 6H5% medium was added to the cells every 2 to 3 days, and they were passaged every 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, the FRTL-5 thyroid cells were used. These cells are a nontransformed rat thyroid cell line in continuous culture that represents a well-defined and reproducible in vitro model of the thyroid gland [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors also reported the high biological stability of this commercial recombinant hTSH preparation, under different conditions, when tested in a cell culture bioassay based on FRTL-5 cells. 24 In our opinion, the optimized formulation and lyophilization conditions of this preparation allow its long-term stability, although some effects of increasing oxidation should be noticed aer several years of storage, as reported by Sendak et al 25 We further emphasize that the RP-HPLC assay proposed here was validated following the ECVAM (the European Centre for Validation of Alternative Methods) guidelines and recommendations. 26,27 This methodology in combination with others, such as isoelectric focusing 28 or capillary zone electrophoresis, 29 can be a powerful tool for batch-to-batch variability evaluation and for recombinant glycoprotein quality assessment along the production process.…”
Section: Discussionmentioning
confidence: 58%